Creative class and regional growth: empirical evidence from eight European countries - Ron A. Boschma; Michael Fritsch (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
We analyze the regional distribution and the effect of people in creative occupations based on data for more than 450 regions in eight European countries. The geographic distribution of the creative class is highly uneven. The creative class is not attracted to highly urbanized regions per se, but rather a climate of tolerance and openness seem to be rather important factors. We find that the creative class has a positive and significant effect on employment growth and new business formation at the regional level. Human capital as measured by creative occupation outperforms indicators that are based on formal education.
Keywords: O31; O18; R12; 330; Creativity; innovation; entrepreneurship; regional development; Unternehmer; Kreativität; Regionale Konzentration; Regionales Wachstum; Westeuropa